Human capital efficiency and firm performance across sectors in an emerging market - Ngoc Phu Tran; Duc Hong Vo (Cogent Business & Management, 2020)
Human capital is considered the cornerstone of any progress in economic growth and development for any country. Vietnam and other emerging markets are no exception. One effect of human capital efficiency on firm performance is considered in various empirical studies. However, the examination of this efficiency on firm performance in Vietnam and other emerging markets has largely been ignored in the current literature, in particular with the use of a value-added intellectual coefficient (VAIC) model, which has been widely used to measure the value added generated by tangible and intangible assets. This paper is conducted to examine the contribution of human capital efficiency to firm performance across 12 sectors in the Vietnamese economy for the period 2011 to 2018. The generalized method of moments (GMM) technique is used in this paper. Empirical results in this paper strongly confirm that human capital efficiency makes a positive contribution to firm performance across sectors in Vietnam. In addition, the findings in this paper indicate that the banking sector does not have the highest level of human capital accumulation as previously thought. In the context of the Vietnamese economy, the level of human capital efficiency varies across sectors and the oil and gas and energy sectors are the best at human capital efficiency. We outline the policy implications from our findings in this study.
Keywords: 650; firm performance; GMM; human capital effiency; VAIC; Vietnam